Peningkatan Kualitas Pendidikan Sekolah Unggulan dan Perguruan Tinggi - Amiruddin Siahaan; Syukri, Makmur; Nazri, Elfin; Azmar, Azmar (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This study examines leading school and college improvement, the research method uses the type of library research, which is a series of activities related to library data collection methods. The results of the study found that to improve the quality of education in schools, various management models and quality improvement strategies could be taken, including Total Quality Management Theory, Organizing Business For Excelency Theory, Four Factor Quality Improvement Models, and Education Quality Improvement through School-Based Management. The strategy to improve the quality of education in schools can be done in the following ways: namely a strategy that emphasizes the results (the output oriented strategy), a strategy that emphasizes the process (the process oriented strategy), and a comprehensive strategy (the comprehensive strategy). As for the challenges in efforts to improve the quality of education in schools, there are many but in essence the inadequate resources of education actors in schools, political will from policy holders and the education policy itself. Some things that must be considered in connection with the strategy to improve the quality of education in universities include Students Who Are Educated, Lecturers as Educators and Teachers, Facilities and Infrastructure